2011
DOI: 10.3928/1081597x-20100310-02
|View full text |Cite
|
Sign up to set email alerts
|

Topography-Guided vs Wavefront-Optimized Surface Ablation for Myopia Using the WaveLight Platform: A Contralateral Eye Study

Abstract: using the WaveLight excimer laser platform for PRK, CDVA and contrast sensitivity outcomes were statistically similar between the wavefront-optimized and topography-guided ablations in eyes with low to moderate myopia with and without astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
5
16
0
Order By: Relevance
“…To the best of our knowledge, this is the first reported study comparing these platforms in photorefractive keratectomy. The findings of our prospective, randomized, fellow-eye study support previous research that the VISX CustomVue wavefront-guided and the WaveLight Allegretto wavefront-optimized platforms are both effective and predictable in photorefractive keratectomy 2426. Falavarjani et al showed that the wavefront-optimized Allegretto platform and a topography-guided platform had similar statistical outcomes 26.…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, this is the first reported study comparing these platforms in photorefractive keratectomy. The findings of our prospective, randomized, fellow-eye study support previous research that the VISX CustomVue wavefront-guided and the WaveLight Allegretto wavefront-optimized platforms are both effective and predictable in photorefractive keratectomy 2426. Falavarjani et al showed that the wavefront-optimized Allegretto platform and a topography-guided platform had similar statistical outcomes 26.…”
Section: Discussionsupporting
confidence: 86%
“…Unlike the wave-front guided lasers, which account for aberrations in the cornea, lens, and retina, topography guided lasers attempt to neutralize corneal irregularities and preserve its aspheric shape 4. Topography-guided lasers are shown to be superior for highly aberrated corneas when wavefront maps cannot be easily obtained 2,5.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited data directly comparing topography-guided with wavefront-based ablations for primary treatments. Falavarjani et al [79] demonstrated similar visual outcomes and contrast sensitivity after PRK with topography-guided ablation in one eye and wavefront-optimized ablation in the fellow eye. In cases of an increased angle kappa, topography-guided ablations centered on the corneal vertex have been shown to better approximate the visual axis than wavefront-guided ablations centered on the pupil [80].…”
Section: Topography-guided Laser Refractive Surgerymentioning
confidence: 71%